Cardiac metastasis from a bronchial carcinoid: report of a case presenting with diffuse thickening of the left ventricular wall. Issue 7 (25th June 2004) - Goddard, M J; Atkinson, C
Abstract : Bronchial carcinoids are low grade malignancies with an excellent prognosis and a low incidence of metastases. This report describes a case of a typical carcinoid tumour with metastases to the spine after four years and to the heart after eight years. Carcinoid tumours rarely metastasise to the heart and previous reports have identified gastrointestinal primaries as the source in most cases. This is the first published case of typical carcinoid tumour that metastasised to the heart from a bronchial primary.